2020
DOI: 10.31080/asop.2020.03.0177
|View full text |Cite
|
Sign up to set email alerts
|

Low Level Light Therapy as an Adjunct Treatment for Meibomian Gland Dysfunction

Abstract: Importance: This study highlights the adjunctive value of low-level light therapy (LLLT) in the management of meibomian gland dysfunction (MGD). Background: To evaluate the effects of LLLT treatment on clinical measures of dry eye related to MGD in patients unresponsive to previous therapies. Design: A retrospective chart review of patients treated at one site. Participants: Fifty eyes of 25 treated patients who were documented treatment failures with previous pharmaceuticals and/or devices were evaluated. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The study design does not allow to discriminate the differential effect of IPL and LLLT, a necessary aim since the effectiveness of the latter is currently supported by very limited evidence. We are only aware of two small studies that applied LLLT alone in patients with DED, obtaining significant improvements in the OSDI, 17 TBUT 16,17 and MGD 17 after 1-3 months. Regarding IPL, although there are several published case series, 13 the strongest evidence on its efficacy comes from some sham-controlled [10][11][12]24 and non-masked comparative 14,27 randomized trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design does not allow to discriminate the differential effect of IPL and LLLT, a necessary aim since the effectiveness of the latter is currently supported by very limited evidence. We are only aware of two small studies that applied LLLT alone in patients with DED, obtaining significant improvements in the OSDI, 17 TBUT 16,17 and MGD 17 after 1-3 months. Regarding IPL, although there are several published case series, 13 the strongest evidence on its efficacy comes from some sham-controlled [10][11][12]24 and non-masked comparative 14,27 randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…This technique uses light-emitting diodes (LEDs) at wavelengths insufficient to produce a thermal effect (often 590–633 nm), but that increases photon intensity and its capacity to penetrate below the skin, inducing cellular photoactivation. 15 In patients with DED, Toyos et al 16 observed a significant increase in Tear film Breakup Time (TBUT) after 3 months of red-light treatment, and Stonecipher et al 17 obtained significant improvements in symptoms, TBUT and MGD after 3 sessions over one week.…”
Section: Introductionmentioning
confidence: 99%
“…Stonecipher., et al showed in a 15-minute session of LLLT used 3 times in one week in dry eye patients who had failed previous pharmacologic, therapeutic, or combination treatments the significant improvements in TBUT (p < 0.001), lissamine green staining (p < 0.02), and MGD grading (p < 0.001) in 3 -5 weeks. In addition to objective findings, subjective improvements in OSDI scores (p = 0.002) were also seen [22].…”
Section: Low Level Light Therapy (Lllt) Solo Therapy (N-232)mentioning
confidence: 86%
“…24 Interestingly, some recent photobiomodulation modalities, such as lowlevel light therapy (LLT), which involves athermal photoactivation, have also been shown to improve dry eye symptoms, tear breakup times, and meibomian gland structure with minimal side effects. 41,42 Future research can compare the effects of BBL-IPL with other athermal treatment modalities like LLT on the improvement of DED from MGD.…”
Section: Safetymentioning
confidence: 99%
“…Figure2Dry eye symptom severity according to the Canadian Dry Eye Assessment (CDEA) questionnaire before and after BBL-IPL therapy. Total scores for the CDEA questionnaire range from 0 to 48 and are interpreted as no dry eye symptoms or normal (<5), mild dry eye symptoms(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate dry eye symptoms(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or severe dry eye symptoms(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
mentioning
confidence: 99%